The Principal Navigations Voyages Traffiques and Discoveries of the English Nation - Hakluyt, Richard (James MacLehose and Sons, 1904)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬